Inovasi Dalam Pembelajaran Di Sekolah Dasar: Studi Peran Guru Dalam Menerapkan Kurikulum Merdeka - Santi, Santi (CV. SINAR HOWUHOWU, 2024)
This study aims to analyze the role of teachers in implementing the Merdeka Curriculum in elementary schools and the learning innovations applied within it. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews, participatory observation, and documentation at several elementary schools that have implemented the Merdeka Curriculum in Gunungsitoli, North Sumatra. The results of the study show that teachers play a central role in developing competency-based learning that aligns with the characteristics of students. Learning innovations include the use of project-based learning, thematic learning, and the integration of technology. However, challenges such as limited facilities and insufficient training remain obstacles to the implementation of the Merdeka Curriculum. This finding suggests the need for ongoing training and improvements in school facilities to support the successful implementation of the curriculum.